Model Terintegrasi Penjadwalan Batch dan Pm dengan Kriteria Minimalisasi Biaya Simpan, Setup dan Pm pada Mesin dengan Increasing Failure Rate - Zahedi Zahedi (Bina Nusantara University, 2013)
Development of today's manufacturing systems leads to the getting shorter in product life cycle, more variety of products, as well as increasing in consumer demand for quality and timeliness. Thus the accuracy and speed of decision-making within the manufacturing system becomes important. This paper proposes an integrated model of batch scheduling and preventive maintenance scheduling, in assumption no non-conforming parts to the criteria of minimizing the total saving cost, setup cost, preventive maintenance cost in minimizing the actual flow time on a machine with increasing failure rate. An example is provided to show how the model and algorithm work.